Eating when depressed, anxious, bored, or happy: Are emotional eating types associated with unique psychological and physical health correlates?. (1st June 2018) - Braden, Abby; Musher-Eizenman, Dara; Watford, Tanya; Emley, Elizabeth
Abstract: The majority of research on emotional eating has examined general emotional eating, to the exclusion of more distinct emotions such as boredom and positive emotions. The current study aimed to examine whether specific types of emotional eating (i.e., eating in response to depression (EE-D), anxiety/anger (EE-A), boredom (EE-B), and positive emotions (EE-P)) were related to a range of psychological (i.e., global psychological well-being, eating disorder symptoms, emotion regulation) and physical health variables. A sample of adults (n = 189) with overweight/obesity were recruited via Amazon Mechanical Turk. Participants self-reported height and weight and completed a battery of questionnaires. Correlational analyses showed that more frequent EE-D, EE-A, and EE-B were related to poorer psychological well-being, greater eating disorder symptoms, and more difficulties with emotion regulation. EE-P was not significantly related to outcome variables. In regression analyses, eating in response to depression (EE-D) was the type of emotional eating most closely related to psychological well-being, eating disorder symptoms, and emotion regulation difficulties. Exploratory analyses revealed associations between EE-D, EE-A, and EE-B and facets of emotion regulation and specific disordered eating symptoms. Findings suggest that unique patterns exist between specific types of emotional eating and psychological outcomes.